TOURNAMENT BRACKET GENERATION FOR MARTIAL ARTS EVENTS: DIGITAL DRAW ALGORITHM - Akhmedzyanov, E.R.; Dmitriev, O.B.; Petrov, P.K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop an efficient digital draw algorithm to generate tournament brackets for the martial arts events. Methods and structure of the study. We developed the digital draw algorithm at the Physical Education Theory and Practice, Gymnastics and Life Safety Department of the Physical Education Institute of Udmurt State University. The digital draw algorithm was developed to complement the computer software toolkit for competitive event design, management and reporting by a Martial Arts Draw section. Generally, the modern martial arts communities set the following requirements for a draw algorithm and resultant tournament brackets: (1) Teammates (of the same regional team and/ or trained by the same coach) should compete at the latest stages; (2) Top-ranking athletes should compete in the finals; and (3) The draw system should be reasonably random, with the brackets expected to never repeat. Every of the above requirements can be met quite simply. Thus, the teammates’ matches may be prevented at the early stages by the tournament brackets with a rational numbering system that secures the teammates of the same region/ coach listed in a sequential manner. Individual competitive accomplishments will be fixed in a database of core events with respect to the ratings. Such rating systems need to be formed separately as provided, for example, in study. On the whole, a competitive draw system will offer a multi-criteria optimization method. Results and conclusion. The digital draw algorithm of our design has been tested beneficial in the Udmurt-Republic-hosted martial arts events, with the digital-draw-algorithm-generated tournament bracket recognized efficient in sorting athletes by their professional skills, competitive ratings, regional teams and coaches. The digital draw algorithm is recommended for application in different sports events that imply draws to group the qualifiers using specific sets of grouping criteria dominated by their professional ranks.